Oracle database upgrade, migration & transformation tips & techniques - Whalen, Edward; Czuprynski, Jim (McGraw-Hill Education, 2015)
This Oracle Press guide provides best practices for migrating between different operating systems and platforms, transforming existing databases to use different storage or enterprise systems, and upgrading databases from one release to the next. Based on the expert authors real-world experience, Oracle Database Upgrade, Migration & Transformation Tips & Techniques will help you choose the best migration path for your project and develop an effective methodology. Code examples and detailed checklists are included in this comprehensive resource.